Uniqueness of Entire Functions concerning Difference Operator - Chun Wu (Abstract and Applied Analysis)
We deal with a uniqueness question of entire functions sharing a nonzero value with their difference operators and obtain some results, which improve the results of Qi et al. (2010) and Zhang (2011).